Facilitating reading for people with dyslexia: a narrative review of recommendations for text formatting - Crivellari Camargo, Murilo; Angelo Barela, José; Faria Teixeira, Letícia; Paschoarelli, Luis Carlos (InfoDesign, 2024)
Dyslexia, a disorder characterized by difficulties in learning to read and write, has aroused interest in many different areas of knowledge, including Information Design. Many recent studies have aimed at testing text formatting variables to design recommendations; however, specific guidelines are still scarce in literature. In this sense, this study conducted a narrative literature review on 19 articles addressing text formatting recomendations for people with dyslexia, including typography, layout, colors, media and images and compared to those stablished by the Dyslexia Style Guide (DSG) (2023). The results reveal that some DSGrecommendations are well accepted among the scientific community while others, as well as some gaps regarding the topic, still require further investigation.